The Social and Historical Impact on the Formation of Russian Medieval Spirituality - Borisovich Lebedev, Alexey; Vladimirovich Tokranov, Alexander; Vladislavovna Kuzmina, Elena (International Journal of Criminology and Sociology, 2022)
This article analyzes the ways of influence of religious worldview on the spiritual life of Western and Eastern Europe. Considering the arguments in favor of the existence of such a phenomenon as a universal «European worldview», the authors conclude that despite the existence of common grounds, the spiritual life of Western Europe and Eastern Europe (in particular Russia) have fundamental differences. The authors pay special attention to the figure of St. Sergius of Radonezh who was the embodiment of Russian medieval spirituality. The Saint harmoniously combined «clever prayer» with practical patriotic activity, thus following the principle of «energetic love». The article also analyzes the «contemplative» and «activity» model of man in the context of the dispute between «Nestyazhateli» and «Iosiflyane». The authors conclude that Russian state policy has been mostly «Iosiflyanian», and the philosophy became a haven for «Nestyazhatel». In conclusion, the authors highlight such a key concept of Orthodox thought as «sobornost», thus noting that in Russian religious thought, human life finds its true meaning only in the human community.